PENINGKATAN KEMAMPUAN MENGENAL HURUF ABJAD DENGAN BALOK HURUF PADA ANAK KELOMPOK B DI KB ILHAM MAUKARO - Ainun, Nur; Ngura, Elisabeth Tantiana; Ita, Efrida; Dua Dhiu, Konstantinus (Jurnal Citra Pendidikan, 2025)
Abstract This study aims to improve the ability to recognize alphabetic letters in early childhood group B in KB Ilham Maukaro through the use of letter blocks. The research method used is class action research (PTK) with qualitative and quantitative approaches. The subjects of this study were 15 children aged 5-6 years. The research was conducted in two cycles, where each cycle consisted of planning, implementation, observation, and reflection stages. Data was collected through observation, interviews, and documentation, then analyzed using qualitative and quantitative descriptive techniques. The results of the study show that the systematic use of letter blocks can improve children's ability to recognize the letters of the alphabet. In the pre-cycle, only 40% of children are able to recognize letters well. After the implementation of learning using letter blocks in the first cycle, the percentage increased t o 65%. Improvements were made in the second cycle, so that children's learning outcomes increased significantly with 90% of children being able to recognize and pronounce the letters of the alphabet well. Children become more active, enthusiastic, and show an overall improvement in literacy skills. Children become more active, enthusiastic, and show an overall improvement in literacy skills. Based on the results of the study, it is recommended that educators in early childhood education (PAUD) use letter block media as an effective learning tool.